Segurança alimentar na África Austral lusófona: o papel da cooperação internacional para o combate à fome entre Brasil, Angola e Moçambique - Schmeling, Guilherme Hoff dos Santos (2025)
Discussions on the promotion of food security gained greater international relevance after the concept was included in discussions on security in the first half of the 1990s. The end of the Cold War allowed food security to become one of the main objectives to be pursued by States based on a constant threat of food shortages on a global scale. This paper aims to analyze the validity of the cooperation signed by Brazil with Angola and Mozambique in relation to the fight against hunger, highlighting what was produced in terms of cooperation, thus identifying whether cooperation has acted as a mitigating or aggravating instrument in the dissolution of food insecurity in the respective countries. Thus, given the analysis of the interaction between State capacities and the predominant agricultural systems, why does food security appear to be a distant objective in the two African countries even from the perspective of Brazilian cooperation? This study is qualitative and explanatory, using a hypothetical-deductive method that tests hypotheses, namely: The persistence of food insecurity in Angola and Mozambique is based on (I) the lack of subsidies to strengthen family farming as a producer and supplier of food, favoring large-scale production based on monoculture for export; (II) food vulnerability circumscribed by the instability of state capacities in African countries, in the face of constant internal conflicts that prevent governments from implementing and strengthening assertive policies to combat hunger; (III) and the conversion of international cooperation into mere technical assistance incapable of producing long-term structuring effects. In seeking an answer to the problem presented, this study will be organized as follows: a first article will analyze the evolution of the discussions on food security within the scope of international relations, based on the contributions of the state capacities approach. The second will focus on the applicability of the theoretical result produced in the first, to be included in the discussion on the fight against hunger within the scope of international cooperation between Brazil, Angola and Mozambique, and will test the hypotheses presented.